2010
DOI: 10.1186/1752-1947-4-267
|View full text |Cite
|
Sign up to set email alerts
|

Cyclosporine-A therapy-induced multiple bilateral breast and accessory axillary breast fibroadenomas: a case report

Abstract: IntroductionBreast adenoma is common. However, in the setting of post-transplantation immune suppression it may be expressed differently.Case presentationA 35-year-old Sudanese woman, with a history of renal transplantation two and half years prior to presentation, was on a single immune suppression therapy in the form of cyclosporine-A since the transplantation. During a regular follow-up visit, she was noticed to have gingival hypertrophy and bilateral breast and axillary swellings. She underwent successful … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(7 citation statements)
references
References 6 publications
(9 reference statements)
0
7
0
Order By: Relevance
“…Their patient had undergone surgical excision for multiple bilateral breast and axillary fibroadenomas (13). Discontinuing the CsA may induce some improvement in early cases, but the breast may not return to its former size due to breast fibrosis, as in our patient (14).…”
Section: Case Reportmentioning
confidence: 94%
“…Their patient had undergone surgical excision for multiple bilateral breast and axillary fibroadenomas (13). Discontinuing the CsA may induce some improvement in early cases, but the breast may not return to its former size due to breast fibrosis, as in our patient (14).…”
Section: Case Reportmentioning
confidence: 94%
“…Yarak et al [13] and Darwish et al [16] reported cases of fi broadenoma in accessory mammary tissue in kidney transplant recipients using Cyclosporine-A. This is one of the drugs that inhibits T-cell activation via calcineurin inhibition.…”
Section: Discussionmentioning
confidence: 99%
“…Consequently, there is an in increase in prolactin blood levels, suggesting infl uence in the steroidogenic function of the ovary and thus affecting the physiological state of the breast. Its chronic use could develop malignant cutaneous tumors and benign mucocutaneous proliferative diseases (fi broadenomas, hypertrichosis, gingival hypertrophy, papillomas, sebaceous hyperplasia and epidermic cysts) [13,16].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…MF in separate quadrants have been excised by incision in the circumareolar region after stringent selection criteria,[ 4 ] or by multiple incisions placed on the breast skin directly over the lumps[ 5 ] with risk of poor esthetic outcome. They have also been removed with round block incision technique which isolates the nipple-areolar complex and by reduction mammoplasty of Rezai and which is a more extensive procedure, particularly suited for patients who have asymmetry of the breasts.…”
Section: Introductionmentioning
confidence: 99%